Observe, practice, and improve: Enhancing sidestep cutting execution in talented female soccer players. A four-week intervention program with video instruction - Nijmeijer, E. M.; Kempe, M.; Elferink-Gemser, M. T.; Benjaminse, A. (The Journal of Strength and Conditioning Research, 2024)
Implicit learning has the potential to improve movement execution and reduce injury risk. Previous research showed beneficial effects of short-term interventions with implicit learning in male athletes. However, research on long-term interventions in female athletes is lacking. The aim of this study was to examine the effects of a 4-week intervention with video instruction on movement execution of SSC, a task that is highly related with anterior cruciate ligament (ACL) injury risk, in female athletes. Twenty talented adolescent female soccer players were part of the control (CTRL, n = 10) or video instruction (VIDEO, n = 10) group. All subjects practiced 4 weeks and received general task instructions. In addition, the VIDEO group received expert video instruction during practice. Lower extremity kinematics and kinetics and vertical ground reaction force of SSC were examined during baseline, immediate post, and 1-week retention tests. After nonlinear registration, differences between each subject and the expert she had seen were determined. These differences were analyzed with SPM1D 2-way ANOVA. No interaction effects between time and group were found (p > 0.05). Main effects of time were found in the frontal plane. In particular, smaller deviations of subjects compared with the seen expert of the knee adduction (p = 0.005, 97.9-100% stance phase [SP]) and hip abduction (p = 0.005, 11.5-13.8% SP) and adduction (p < 0.001, 33.4-87.7% SP) moments were found in immediate post compared with baseline. These frontal plane short-term improvements, replicating earlier findings in both sexes, may lower ACL injury risk. The large observed interindividual differences over time may have concealed the long-term effects of video instruction at the group level.